Tingkat Kepuasan Pemustaka Terhadap Aplikasi iSumbar Mambaco Menggunakan End User Computing Satification (EUCS) - Harianto, Dika; Erlianti, Gustina (Scinary, 2023)
The purpose of this research was to describe the level of satisfaction librarians had towards the iSumbar Mambaco application by utilizing the End User Computing Satisfaction (EUCS) method. This method focused on end users' satisfactions towards the use of the information system by evaluating the Content, Accuracy, Format, Ease of Use, and Timeliness. The research method used was a descriptive method done by obtaining the data directly from the observed field. The objects researched were iSumbar Mambaco's librarians which were 95 respondents that were chosen randomly. The technique of data collection was distributing questionnaires in the form of Google Form that were sent through WhatsApp. The data analysis was done by using Likert scale. Based on the result of the research, the level of satisfaction the librarians had towards the iSumbar Mambaco application was averaging at 2,97. This showed that the satisfaction level of the librarians was at level 3 (positive). The Accuracy dimension yielded the highest mean score at 3,13, while the lowest score was achieved by the Timeliness dimension with the mean score of 2,80.